2009
DOI: 10.1016/j.jenvman.2009.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Understanding behaviour to inform water supply management in developed nations – A review of literature, conceptual model and research agenda

Abstract: Water is a scarce resource in many parts of the developed world. Two solutions are possible to address water scarcity: conservation of existing resources, or the further production of water from new sources e.g. through recycling of wastewater or desalination of seawater. However, the main hurdle to implementation of many of these solutions is often viewed as a lack of public willingness to adopt these alternative water behaviours. Research in this area is therefore crucial. Yet, and possibly due to the interd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(71 citation statements)
references
References 90 publications
2
68
0
1
Order By: Relevance
“…Many studies are found in the fields of recycling [10][11][12][13][14], electricity saving [15][16][17][18][19], and water saving behaviors [20][21][22]. However, each study mainly focuses on one particular PEB, and studies comprehensively dealing with various PEBs are rarely found.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies are found in the fields of recycling [10][11][12][13][14], electricity saving [15][16][17][18][19], and water saving behaviors [20][21][22]. However, each study mainly focuses on one particular PEB, and studies comprehensively dealing with various PEBs are rarely found.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is somewhat inconsistent with other studies: a nationwide study of the US found that the majority of participants are aware of water scarcity issues and want to see reforms to improve these problems [48], which was similar to another study in Colorado [49]. Studies in Australia have found that individuals are only somewhat aware of water scarcity issues, and have found further education is needed to enhance public knowledge about water scarcity issues [50,51]. There is no known survey of Canadians' perceptions of water scarcity, therefore any direct comparison of the findings is not possible.…”
Section: Theme: Scarcitymentioning
confidence: 56%
“…If water awareness campaigns have to fulfill their potential and leave a longer imprint in the behavior of water users (Wang et al, 1999;Hurlimann et al, 2009;Saurí, 2013) it is fundamental that they take into account the dynamic residential and sociodemographic characteristics as well as the water use habits of the population targeted. Thus, it is crucial to ascertain whether recommendations for particular behaviors are grounded on a sound appraisal of existing water habits.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral change regarding water consumption is perhaps one of the most sought-after objectives of water conservation policies, especially during times of drought (Hurlimann et al, 2009;Jorgensen et al, 2009;Fielding at al., 2012). To this end, water planning and management must consider awareness campaigns as a tool to reduce water demand and therefore ease drought impacts as well as the pressures on the development of new water supply sources (Michelsen et al, 1999).…”
Section: Water Awareness Campaigns During Drought Periods: Strengths mentioning
confidence: 99%